Engineering documentation control handbook configuration management in industry. - Watts, Frank B.
Control of engineering documentation, sometimes called Configuration Management (CM) especially in the defense industries, remains critical to world-class manufacturing survival. The 3rd edition of this popular engineering documentation handbook improves upon one of the best blueprints for efficient EDC/CM ever published, and continues to provide a significant company strategy for managers, project leaders, chief engineers and others. It can be used in many industries to improve the control of engineering documentation.